Theoretical investigation of the growth mechanism of gold thiolate nanoparticles - Barngrover, Brian Michael (Kansas State University, 2015)
This body of work describes a theoretical study of the growth mechanism of gold thiolate nanoparticles from Au(III) as synthesized in the Brust-Schiffrin method. The Au(III) salt can be reduced to form Au(I) by two thiols or a hydride. Depending on the polarity of the solvent, the Au(I) species will either yield rings and anionic chains, remain in isolation, or create an ionic complex with the phase transfer agent. No matter what form the Au(I) species takes, a second reduction must occur to yield Au(0). If the solvent is polar, such as methanol or water, and the Au(I) species is a ring or anionic chain, then a hydride can reduce the structure and create a gold-gold bond and dissociate a thiol from the structure. The gold atoms involved in the gold-gold bond would have a formal Au(0) oxidation state. However if the Au(I) species can be kept from forming rings or chains in the polar solvent or if the system is in a nonpolar solvent, then two Au(I) species in close proximity in the presence of hydride can react to yield a non-radical Au(0) species. The oxidation of bare gold nanoclusters by thiol will also be examined, such as in the case of SMAD-produced gold nanoparticles. In this process, the gold nanoclusters are initially in the Au(0) oxidation state. However the SR-Au-SR “staple” motifs that are known to passivate gold nanoparticles contain Au(I) species. The adsorption of thiol on various sizes of gold clusters in several charge states will be calculated and the mechanism for the oxidation of Au3 and three-dimensional Au12 will be modeled. The rate-limiting step is found to be the thiol hydrogen dissociation onto the gold cluster. Once this dissociation occurs, the hydrogen can move freely around the surface. Finally, Au25(SH)18- will be investigated as a catalyst for selective hydrogenation of α,β-unsaturated aldehyde. The dependence of the energetics of hydrogen gas dissociation on Au25(SH)18- on the functional and Grimme dispersion correction employed will also be examined.
Keywords: DFT; Gold thiolate; Growth mechanism; Catalysis; Chemistry (0485); Nanoscience (0565); Physical Chemistry (0494)